Analisis Patologi Sosial terhadap Kasus Pencurian Ringan di Lingkungan Kos Mahasiswa - Citra Nanda Purba; Evika Kartika Sari Lawolo; Nova Novita Siregar; Sherina Silaban; Sani Susanti (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes the phenomenon of petty theft occurring in a student boarding house environment through the perspective of social pathology. The research is motivated by repeated incidents of minor theft that disrupt the sense of security and social order among students living in kost. Using a qualitative descriptive approach, data were collected through observation and in-depth interviews with several student residents who experienced or witnessed petty theft. The findings reveal that petty theft behaviors are influenced by economic pressure, opportunity factors, weak social control, and low moral awareness. The behavior is categorized as a form of social pathology because it violates norms, disrupts social harmony, and leads to distrust among residents. The study also highlights the impacts experienced by victims, including financial loss, anxiety, and decreased social cohesion. Preventive efforts identified include strengthening social control, increasing awareness among residents, and improving the security system within the boarding environment. This research contributes to understanding how social pathology manifests in everyday student life and offers insights for prevention in similar environments.